Social intelligence of cadets of the security and defence sector higher education institutions who receive higher education in the specialities of “Law” and “Psychology” - S. V. Kharchenko; O. V. Koldashov (Bulletin of Kharkiv National University of Internal Affairs)
The article emphasises that for the actors of the security and defence sector, solving various communication situations is a constant and important task which can become difficult to perform if the social intelligence abilities are not sufficiently developed.